IDENTIFICATION OF CHARACTERISTICS OF SCHIZOPHRENIA PATIENTS IN MENTAL HOSPITAL - Rindayati, Rindayati; Nasir, Abd; Kurniawan, Yeri; Iswatun, Iswatun; Harianto, Susilo; Sofiatun, Sofiatun; Fadilah, Firsca Nur (Journal of Vocational Nursing, 2024)
Introduction: Schizophrenia is a group of disorders characterized by hallucinations, delusions, changes in thought flow, affect, and agitation. This disease attacks people of various ages, genders, and educational and economic levels. The purpose of this study is to identify the characteristics of patients with schizophrenia in mental hospitals. Methods: This quantitative research used a descriptive approach, with a sample of 319 patients. Data was taken using a purposive sampling technique, the data source was from the medical records of the Menur Mental Hospital, Surabaya in January-March 2023. Variables, namely the characteristics of schizophrenia patients, include age, gender, education, employment, and marital status. Data analysis uses quantitative description. Results: The average age of patients is 25-44 years with a mean value (2.78), the largest age is 25-44 years (37.6%), 3-4 years (20.1%), a small percentage is >65 years (4.4 %), there were more men (63.3%) than women, the majority, 77.1%, did not work, the majority of patients had a high school or equivalent education (36.7%), and 68% were not married. Conclusions: Characteristics of schizophrenic patients, most of them are adults, men, not working, lower middle school education, and not married. Identification of important characteristics is used as basic information in early patient treatment.